Involvement of Teachers and Parents in Developing Social Interaction of Autistic Students in Schools - Phytanza, Diajeng Tyas Pinru; Umar, Veroyunita; Mumpuniarti, Mumpuniarti; Rahmawati, Rafika (Universitas Negeri Malang, 2024)
This study aims to determine the form of involvement of teachers and parents in developing social interaction of autistic children at school. The instruments used in this study were developed based on the theory of teacher and parent involvement according to Epstein (2010), which includes six typologies: parenting, communication, volunteering, learning at home, decision-making, and collaborating with the community. The research was conducted by disseminating an online questionnaire using a Google form. The data analysis technique used is quantitative descriptive with pivot table analysis. The data is grouped into Excel format based on the research problem, calculated using pivot table analysis, and the results are interpreted as a pivot chart. The results of the study show that most teachers have provided training to parents on how to improve children's social interaction skills, but collaboration with outside parties is still minimal. Most parents have also actively taught their children how to interact socially well.